Acute Care for Elders (ACE) Team Model of Care: A Clinical Overview - Kellie L. Flood (Geriatrics, 2018)
The Institute of Medicine (IOM) Reports of To Err is Human and Crossing the Quality Chasm have called for more interprofessional and coordinated hospital care. For over 20 years, Acute Care for Elders (ACE) Units and models of care that disseminate ACE principles have demonstrated outcomes in-line with the IOM goals. The objective of this overview is to provide a concise summary of studies that describe outcomes of ACE models of care published in 1995 or later. Twenty-two studies met the inclusion. Of these, 19 studies were from ACE Units and three were evaluations of ACE Services, or teams that cared for patients on more than one hospital unit. Outcomes from these studies included increased adherence to evidence-based geriatric care processes, improved patient functional status at time of hospital discharge, and reductions in length of stay and costs in patients admitted to ACE models compared to usual care. These outcomes represent value-based care. As interprofessional team models are adopted, training in successful team functioning will also be needed.